Learning while creating value for sustainability transitions: The case of Challenge Lab at Chalmers University of Technology. (20th January 2018) - Larsson, Johan; Holmberg, John
Abstract: To achieve a sustainable future, a variety of societal systems need to be transformed and new ways of social collaboration created. Higher education institutions play an important role in guiding these changes, through education, research, and outreach. In this paper, we study a lab-based learning environment, the Challenge Lab, where master's degree students engage in, and create value in support of, the transition to a sustainable society. Three student cases are analyzed in-depth to understand how the Lab functions as an expansive learning process and provides space for transformative and integrative value creation. The Lab's guiding methodology is based on backcasting from principles, combined with clarifying the students' core values and drivers. The role of the teacher in such a learning environment is to provide the basis for the process by facilitating and guiding. Provided with the right conditions, these students have the ability to challenge underlying assumptions about how systems work and to build trust by facilitating dialogue among actors in society. The students perceived the opportunity to engage in real-world challenges as meaningful, drew valuable lessons for their future, and got to know themselves better. In this transitional period of achieving ambitious sustainability goals and targets, students' ability to be a source of change – maybe the most important source inside higher education institutions – deserves much more attention.